(3GdcaGAI GdEfJGLjI hGdGbJUGOjI deMUhd bUH GdScQ (B( (3GdZQS (B) (3ai LeghQjI eUQ GdYQHjIs - (3gOgO, MGeO YHO GdTGai(B.s; (3YUQ, eMeO HOjQ GdehGai(B.s (2010)
(3jgOa GdHMK Edi bjGS cd ef GdcaGAI GdEfJGLjI hGdGbJUGOjI hPdc HOQGSI OGdGJ GdGfJGL hGdJcGdja deMUhd bUH GdScQ GdZQS ai Cge efGWb GdGfJGL HLeghQjI eUQ GdYQHjI ddJYQa Ydi eOi GSJNOGe GdefJLjf ddehGQO GdEfJGLjI GdeJGMI HGdTcd GdPi JJMbb eYg GdcaGAI GdEfJGLjI hGdGbJUGOjI(B.s
(3jMJhi Ydi eQGLY(B.s
(3edNU HGddZI GdCfLdjRjI(B.s
1
Keywords: (3bUH GdScQs -- (3GbJUGOjGJs; (3bUH GdScQs -- (3eUQs